Modelling contents status for IPTV delivery networks - Mohamed Fati, Suliman; Sumari, Putra; Yuhaniz, Siti Sophiayati; Amir Sjarif, Nilam Nur (2017)
Since IPTV has been invented, IPTV is considered a dominant technology to distribute high quality videos and live channels anytime anywhere over challenging environment to end users who are having different preferences and demands. Presently, IPTV service providers manage IPTV delivery networks, in terms of contents, channels, resources, based on contents popularity distribution and/or users’ preferences only. Although content popularity and users’ preferences play an important role to cope with the increasing demand of IPTV contents/channels, these two measures fail in producing efficient IPTV delivery networks For that, IPTV delivery network designing should integrate the IPTV content characteristics like size, interactivity, the rapid changing lifetime. Therefore, the idea of this paper is to build a mathematical model that integrates all these factors in one concept called IPTV content status. Modeling the contents status according to its characteristics is an important point to design Content-Aware IPTV delivery networks.The experimental results showed the superiority of modeling IPTV content status in balancing the load and reducing the resources waste.